QUO VADIS HUKUM ISLAM (ANTARA IDEALITAS DAN REALITAS INDONESIA) - Dinda Izzati (JURNAL INDO-ISLAMIKA, 2018)
Evidently, a few months after the Jakarta Charter was signed, Christian circles from Eastern Indonesia submitted an ultimatum, if the seven words in the Jakarta Charter were still included in the Preamble to the 1945 Constitution, then the consequence was that they would not want to join the Republic of Indonesia. The main reason put forward by Pastor Octavian was that Indonesia was seen from its georaphical interests and structure, Western Indonesia was known as the base of Islamic camouflage, while eastern Indonesia was the basis for Christian communities. Oktavianus added that Christians as an integral part of this nation need to realize that they also have the right to life, religious rights, political rights, economic rights, the same rights to the nation and state as other citizens, who in fact are mostly Muslims. This paper aims to determine and understand the extent to which the basic assumptions of the Indonesian people view the role of Islam as presented in an exclusive format.